Determination of Re, Os, Ir, Ru, Pt, Pd Mass Fractions and 187Os/188Os Ratios of Organic‐Rich Geological Reference Materials. Issue 2 (11th April 2022) - Wang, Mengjie; Chu, Zhuyin; Meisel, Thomas C.; Guo, Jinghui
Abstract : At present, reported data for Re‐PGE mass fractions (in particular) and 187 Os/ 188 Os isotope ratios of organic‐rich reference materials (RMs) are rare, hampering the comparison of data quality between different laboratories. In this study, we measured the Re‐PGE (Os, Ir, Ru, Pt and Pd) mass fractions, as well as 187 Os/ 188 Os isotope ratios of five shale RMs, including USGS SGR‐1b (oil shale), SBC‐1 (marine shale), SCo‐2 (silty marine shale), ShTX‐1 (calcareous organic‐rich shale) and ShCX‐1 (calcareous shale), and one oil RM, NIST RM 8505. The results show that the five shale RMs have similar upper continental crust‐normalised PGE‐Re patterns and are generally homogeneous in Re‐PGE mass fractions and 187 Os/ 188 Os isotope ratios at test portions of 0.2–0.5 g, and thus can be used as matrix‐matched RMs for Re‐Os and PGE of shale samples. The oil RM NIST 8505 and its asphaltene separates are also roughly homogeneous in Re‐PGE mass fractions and 187 Os/ 188 Os isotope ratios at test portions of 0.1–0.3 g and can potentially be used as an oil RM for Re‐Os and PGE. Abstract : Key Points First report of PGE mass fractions in five USGS shale RMs and NIST RM 8505. First report of 187 Re/ 188 Os and 187 Os/ 188 Os for USGS RMs ShTX‐1 and ShCX‐1. Our data indicate that these RMs can be used for data quality control for Re‐Os and PGE measurements in organic‐rich geological materials.